Traumatic arteriovenous fistula of the left ulnar artery and vein - Obiozor AA; Obiozor DC (Ibom Medical Journal)
Traumatic arteriovenous fistulae (AVFs) result from a puncture of adjacent artery and vein, leading to a low-resistance, high-pressure gradient with consequent high flows. Flow in the supplying artery exhibits a high-velocity, low-resistance waveform, while the draining vein shows arterial-type pulsations. At the fistula site, high-velocity flow jets can produce ambiguous and confusing color and spectral Doppler signals, with possible artefacts from adjacent tissue vibration. Distal to the fistula, hemodynamics may be altered, and vascular steal syndrome is possible. A 45-year-old male construction worker presented with a gradually enlarging, pulsatile swelling on the volar aspect of his left wrist for two months. He reported a throbbing sensation and occasional numbness in his left hand with a history of wrist trauma. Doppler ultrasound confirmed an arteriovenous fistula between the ulnar artery and vein with preserved brachial artery flow. Blood tests showed normal renal function with no evidence of infection or inflammation. He was diagnosed with multiple arteriovenous fistulous formations of the ulnar artery and vein and referred for surgical repair. He underwent successful surgical correction and was followed up at regular intervals to monitor for recurrence. Timely diagnosis and surgical intervention are necessary to prevent complications such as venous insufficiency, thrombosis, or limb ischemia.